Spontaneous portosystemic shunt diameter predicts liver function after balloon‐occluded retrograde transvenous obliteration. Issue 2 (28th January 2022) - Tatsumi, Akihisa; Maekawa, Shinya; Osawa, Leona; Katoh, Ryo; Komiyama, Yasuyuki; Nakakuki, Natsuko; Takada, Hitomi; Matsuda, Shuya; Muraoka, Masaru; Suzuki, Yuichiro; Sato, Mitsuaki; Takahashi, Ei; et al.
Abstract: Background and Aim: Recently, balloon‐occluded retrograde transvenous obliteration (BRTO), performed for spontaneous portosystemic shunts (SPSS), has been receiving attention as a measure to improve liver function in cirrhotic patients with portal hypertension. However, it is unclear whether SPSS diameter is associated with changes in hepatic venous pressure gradient (HVPG) and liver function after BRTO. Methods: In 34 cirrhotic patients receiving BRTO for hepatic encephalopathy/gastric varices, the association of SPSS diameter with liver function at baseline and 6 months after BRTO and the accompanying changes in HVPG were investigated. Results: Patients had Child–Pugh (CP) scores of A/B/C (7/19/8), SPSS diameters of ≤10 mm/11–20 mm/<20 mm (8/21/5), and an average observation period of 3.2 (0.3–8.5) years. SPSS diameter was significantly associated with male sex, alcohol use, and values of albumin, prothrombin time (PT%), and NH3 at baseline. Moreover, the SPSS diameter was significantly correlated with the changes in HVPG observed upon BRTO ( r = 0.55, P = 0.005), and a large shunt diameter was significantly associated with a greater increase in HVPG. At 6 months, significant improvements in albumin, PT%, bilirubin, and NH3 were observed overall, but the improvement was marked in those with larger shunt diameters if they had CP A/B. Conclusion: SPSS diameter was strongly associated with liver function at baseline and after BRTO and also with changes in HVPG, indicating that SPSS diameter is an important predictor of BRTO outcome. Abstract : Liver function in liver cirrhosis was negatively associated with the SPSS diameter, and an increase in shunt diameter was accompanied by an exacerbation of liver dysfunction. HVPG increase (ΔHVPG) observed after BRTO was significantly associated with the SPSS diameter. The improvement in liver function with BRTO was dependent on the SPSS diameter, especially when liver function was preserved in the Child–Pugh A or B range.